2018
DOI: 10.1002/ecm.1324
|View full text |Cite
|
Sign up to set email alerts
|

Egg boon fatty acids reveal effects of a climatic event on a marine food web

Abstract: Flow of essential fatty acids (EFAs) through food webs is critical for the health of individual animals, populations, and communities. Planktonic eggs may play a central role in marine systems because they are highly concentrated in EFAs, superabundant, and consumed by a variety of species. Previous research suggests that egg fatty acid composition should not be useful for trophodynamic studies because it should be tightly regulated to meet the nutritional needs of embryos. Eight years of sampling the egg boon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This suggests that dietary EPA and ALA were not retained in the salmon tissues, but instead likely used for the synthesis of DHA by fish in both dietary treatments (Kainz et al, 2006). Besides internal synthesis of DHA (Murray et al, 2014;Taipale et al, 2018) individuals also could attain high DHA via dietary retention before the experiment and through the maternal provisioning of eggs from which they hatched (Fuiman, 2018). Despite a higher bioaccumulation factor, the DHA content was lower in both muscle and brain tissues n − 3 of the salmon fed on the n − 3 LC-PUFA-deprived diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that dietary EPA and ALA were not retained in the salmon tissues, but instead likely used for the synthesis of DHA by fish in both dietary treatments (Kainz et al, 2006). Besides internal synthesis of DHA (Murray et al, 2014;Taipale et al, 2018) individuals also could attain high DHA via dietary retention before the experiment and through the maternal provisioning of eggs from which they hatched (Fuiman, 2018). Despite a higher bioaccumulation factor, the DHA content was lower in both muscle and brain tissues n − 3 of the salmon fed on the n − 3 LC-PUFA-deprived diet.…”
Section: Discussionmentioning
confidence: 99%
“…An important but poorly understood consequence of climate change is the reduced availability of omega-3 long-chain polyunsaturated fatty acids (n − 3 LC-PUFA), eicosapentaenoic acid (EPA, 20:5 n − 3) and docosahexaenoic acid (DHA, 22:6 n − 3), in aquatic food webs (Fuiman, 2018;Hixson & Arts, 2016;Taipale et al, 2018). This issue is especially pressing in temperate headwater streams vulnerable to rapid decrease of these micronutrients because increasing temperature (Hixson & Arts, 2016) and frequency of extreme weather events, such as torrential rains (Kanno et al, 2014;Woodward et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding seasonality, the increment in the PUFA content during summer and autumn and a higher DHA/EPA ratio in autumn with both patterns mostly observed in the digestive gland, could be explained by changes in the diet that would be lately detected in the FA profile as shown in other cases (e.g., Hardy and Keay, 1972;Tir et al, 2015;Fuiman, 2018). Apart from the season, we observed other time-related variations associated to the sampled year, particularly in 2004 and 2005, when differences were mainly apparent in the FA profile of the digestive gland.…”
Section: Fatty Acid Compositionmentioning
confidence: 92%
“…Batch-spawning fishes that continue to feed during spawning periods largely depend on recent diets for nutrients that are deposited in eggs [3,4], which provides an opportunity to understand trophic flow of FA through egg boons. A recent field study, for example, reported substantial interannual variation in FA composition of eggs of a batch-spawning marine fish and demonstrated that this variation was associated with climate-driven changes in prey availability [5].…”
Section: Introductionmentioning
confidence: 99%